Life Skills in a Minute: Sending a Card - Heather M. Janney (EDIS)
Most of us have received a greeting card at some point in our lives. Receiving a card in the mail is an experience: pulling it out of the mailbox, reading the outside of the envelope, breaking the seal, pulling out the card, reading the note from the sender, and then placing it somewhere special. This new 3-page publication of the UF/IFAS 4-H Youth Development program provides some guidelines to help with sending greeting cards. Written by Heather Janney.